1969
DOI: 10.1136/bmj.1.5639.289
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Viraemia in Babies Infected with Rubella Virus before Birth

Abstract: MEIAJOU 289that during long-term therapy the plasma digoxin ooncentration reflects the tissue concentration because of a fairly predictable plasma: tissue distribution ratio. All the patients with digoxin toxicity reported here had been previously digitalized and intoxication occurred during the process of chronic therapy as a result of the slow accumulation of digoxin. In this clinical context it is possible to cautiously plan a therapeutic approach to the problem on the basis of the results obtained.If an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The presence of RV antigens was shown by immunofluorescence (Fig. Long-term viraemia occurs in the context of congenital infection [21], and live vaccine strains replicate in lymphocytes of immunocompetent vaccinized individuals for several weeks [22]. Although we cannot definitely exclude a bystander effect for this skin-tropic virus, its absence in healthy skin samples distant from granuloma lesions and the serum of index cases rules out widespread dissemination of RV in a context of immunodeficiency, and strongly supports a causal role for RV in granuloma formation in paediatric PID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of RV antigens was shown by immunofluorescence (Fig. Long-term viraemia occurs in the context of congenital infection [21], and live vaccine strains replicate in lymphocytes of immunocompetent vaccinized individuals for several weeks [22]. Although we cannot definitely exclude a bystander effect for this skin-tropic virus, its absence in healthy skin samples distant from granuloma lesions and the serum of index cases rules out widespread dissemination of RV in a context of immunodeficiency, and strongly supports a causal role for RV in granuloma formation in paediatric PID.…”
Section: Discussionmentioning
confidence: 99%
“…RV replicates in monocytes and also in activated B-lymphocytes and T-lymphocytes [19,20]. Long-term viraemia occurs in the context of congenital infection [21], and live vaccine strains replicate in lymphocytes of immunocompetent vaccinized individuals for several weeks [22]. RV capsid inhibits Fas-dependent apoptosis mediated by Bax, and it has been suggested that this may allow within-host viral dissemination by way of apoptosis-resistant infected lymphocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…cells. Rubella virus may be isolated from blood cells obtained from patients with rubella (10)(11)(12). Using unpurified, PHA-stimulated and unstimulated leukocyte cultures infected with varying doses of virus, Mellman et al 20found that virus persisted for a longer time in the presence of cells than in their absence.…”
Section: Discussionmentioning
confidence: 99%
“…After the report of the isolation of rubella virus in 1962 (7) it was found that infants with congenital rubella had prolonged infections (7)(8)(9)(10)(11)(12)(13)(14); viremia occurred and leukocytes were found to be infected. In contrast, persistent infection was not noted in postnatal illnesses due to rubella virus.…”
Section: Discussionmentioning
confidence: 99%